Analisis Pergerakan Vertikal Titik Pantau Jembatan Penggaron, Kabupaten Semarang, Propinsi Jawa Tengah - Yacob Victor Hayer; T Aris Sunantyo; Nurrohmat Widjajanti (P3M- Politeknik Negeri Kupang, 2020)
Penggaron bridge toll highway is located in road Semarang-Ungaran, 20th kilometer in the Susukan region, East Ungaran, Semarang regency, Central Java province. Penggaron bridge has a 400 m length and nine pillars that support the weight of the bridge. This bridge has began operation since 2010. The bridge visually deformed as indicated by small cracks in the pillars of the bridge. Natural factors such as unstable soil conditions are suspected as the cause of deformation. To minimize and prevent damage that may occur on the bridge then the Penggaron bridge deformation monitoring should be performed. Therefore, this study analyze the vertical movement on the Penggaron bridge using height difference observation data by waterpass in 2014 s.d. 2015. This study used four epoch height different observation data on the 18 bridge monitoring points. The 18 monitoring bridges points was tied to two reference points around the bridge. These observation data is processed by Least Squares Adjustment parameter method to get the height and its standard deviation, vertical movement and its standard deviation, vertical movement velocity and its standard deviation as well as average velocity and average acceleration on every bridge monitoring points on each epoch. The next step includes the computation and analysis of vertical movement, as well as the significance of two parameter different test. The results of this study are the vertical movement vector of the 18 monitoring points with magnitude from 3,1 mm to 170,3 mm with the majority down direction. The vertical movement velocity has a range between 3,05 mm/month to 89,35 mm/month with the movement direction tends to downward. The average velocity of vertical movement for epoch I and II is 7,08 mm/month, epoch II and III is 4,93 mm/month, epoch I and III is 6,00 mm/month, epoch III and IV is 6,03 mm/month, epoch I and IV is 1,29 mm/month with the movement direction tends to downward. The average acceleration of vertical movement for epoch I and II is 7,08 mm/month2, epoch II and III is 4,93 mm/month2, epoch I and III is 3,00 mm/month2, epoch III and IV is 6,03 mm/month2. The majority of the significance of two parameter different test parameters is rejected, it means that monitoring points had a significant movement.